USM SCIENTISTS HONOURED WITH PRESTIGIOUS AWARDS IN KOREA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
Three Universiti Sains Malaysia (USM) professors from the Engineering Campus have once again put the USM name in the limelight after being honoured with a number of prestigious major awards in Seoul, South Korea on 4 December 2016.